2003
DOI: 10.1136/pmj.79.936.602
|View full text |Cite
|
Sign up to set email alerts
|

Systemic absorption of FD&C blue dye associated with patient mortality

Abstract: The addition of FD&C blue dye to enteral feeds is a common practice in hospitals to detect aspiration. However, the degree of systemic absorption and safety of this dye in critically ill patients has not been studied. A patient with sepsis who died after systemic absorption of FD&C blue dye No1 is described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…Of these, brilliant blue and patent blue are the most common additives, although patent blue is banned in the United States, and no permission was sought for brilliant black, while fast green is banned in the EU. These colorants are not readily absorbed by our bodies, in fact, 95% of them are present in feces, and there are no reports of deaths due to human improper absorption (Gaur and others ). Reports on changes in mitochondrial respiration have been described (Reyes and others ), as well as somatic mutation in Drosophila melanogaster wing spot test (25 mg/mL of patent blue, 12.5 mg/mL amaranth) (Sarikaya and others ; Tanaka and others ).…”
Section: Types Of Additivesmentioning
confidence: 99%
“…Of these, brilliant blue and patent blue are the most common additives, although patent blue is banned in the United States, and no permission was sought for brilliant black, while fast green is banned in the EU. These colorants are not readily absorbed by our bodies, in fact, 95% of them are present in feces, and there are no reports of deaths due to human improper absorption (Gaur and others ). Reports on changes in mitochondrial respiration have been described (Reyes and others ), as well as somatic mutation in Drosophila melanogaster wing spot test (25 mg/mL of patent blue, 12.5 mg/mL amaranth) (Sarikaya and others ; Tanaka and others ).…”
Section: Types Of Additivesmentioning
confidence: 99%
“…In two recent studies by Gaur et al (2003) and Lucarelli et al (2004) three cases of refractory shock and metabolic acidosis in critically ill patients are reported. The patients received Brilliant Blue FCF added to enteral nutrition formulations in order to facilitate the detection of aspiration.…”
Section: Human Studiesmentioning
confidence: 99%
“…According to Lucarelli et al (2004), the dose did not exceed 0.7 mg/kg bw/day for the first patient and 2 mg/kg bw/day for the second one. The dose was not mentioned by Gaur et al (2003). Although in healthy subjects absorption of Brilliant Blue FCF appears to be limited, critically ill patients have increased gastrointestinal permeability to Brilliant Blue FCF secondary to enterocyte death and stress induced release of neuro-endocrine factors in the intestinal epithelium.…”
Section: Human Studiesmentioning
confidence: 99%
“…On the other hand, C15, C16, C18, C20, C14:1 and C18:2 were sharply increased more than control to 4.32, 47.92, 9.74, 9.09, 3.03 and 14.06%, respectively, but C17was greatly decreased from 50.50% in the control rat feces to 0.43% in treated rat feces. Data in Table (5) indicated that, the appearance or incriminate of some fatty acids in treated rat feces, may be due to form a new complex between them and synthetic flavourants more than 80% of food additives were secreted in rat feces (Gaunt et al, 1972, FAO/WHO, 1974, Phillips et al, 1980Maha, 1990;Gaur et al, 2003;Saad et al, 2005;Yoshikawa et al, 2011;Sarikaya et al, 2012).…”
Section: Synthetic Food Flavourantsmentioning
confidence: 99%
“…It must be born in mind that, with the exception of a few special cases of hypersensitivity to a variety of chemicals including certain additives, no direct evidence has emerged to incriminate any synthetic food additives among the factors responsible for serious illness in man (Lucova et al, 2013), about 20% of synthetic food colourants and more of synthetic food flavourants are absorbed from gut (Gaur et al, 2003;Sarikaya et al, 2012), moreover, they possess a wide range of biological and physiological effects on the metabolism of animals (FAO/WHO 1974;Abdel-Rahim et al, 1992;Tanaka 2006;Tanaka et al, 2008;Gao et al, 2011).…”
Section: Introductionmentioning
confidence: 99%